2018
DOI: 10.3390/ijms19113322
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Systems for Intra-Articular Delivery of Mesenchymal Stromal Cells for Cartilage Treatment: A Systematic Review of Preclinical and Clinical Evidence

Abstract: Stem cell-based therapy is a promising approach to treat cartilage lesions and clinical benefits have been reported in a number of studies. However, the efficacy of cell injection procedures may be impaired by cell manipulation and damage as well as by cell dissemination to non-target tissues. To overcome such issues, mesenchymal stromal cell (MSC) delivery may be performed using injectable vehicles as containment systems that further provide a favorable cell microenvironment. The aim of this systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 91 publications
0
21
0
Order By: Relevance
“…The development of articular stem cell therapies is promising, since these cells have the ability for self-renewal and differentiation into osteogenic or chondrogenic lineages (Canadas et al, 2018). HA injection therapies, combined with MSCs from BM, are currently under investigation for bone and cartilage tissue regeneration (Kaleka et al, 2018;Roffi et al, 2018), (Fig. 7).…”
Section: Therapeutic Applications Of Ha Including Cell Therapymentioning
confidence: 99%
“…The development of articular stem cell therapies is promising, since these cells have the ability for self-renewal and differentiation into osteogenic or chondrogenic lineages (Canadas et al, 2018). HA injection therapies, combined with MSCs from BM, are currently under investigation for bone and cartilage tissue regeneration (Kaleka et al, 2018;Roffi et al, 2018), (Fig. 7).…”
Section: Therapeutic Applications Of Ha Including Cell Therapymentioning
confidence: 99%
“…To minimise those issues, injectors sought different injectable vehi-cles as containment systems to provide a better microenvironment for injected cells. Roffi et al 12 reviewed 40 studies (19 preclinical and 21 clinical trials) with platelet-rich plasma (PRP), hyaluronic acid (HA) and hydrogels to help delivery and function of MSC. Even though the authors reported negligible adverse events and promising clinical outcomes, the prevalence of low-quality studies prevented demonstration of benefit, calling for studies designed to more clearly demonstrate possible improved outcomes.…”
Section: Autologous Mesenchymal Stem Cellmentioning
confidence: 99%
“…The association of MSCs with HA to treat cartilage has been studied in different species, mostly animal models. Although the treatments are safe and promising results are observed, it is still not possible to draw conclusions on their real benefits, due to the limitations inherent to artificial models and to the heterogeneity and low quality of many of the clinical studies (Roffi et al, 2018). It has been stressed that the use of naturally occurring diseases in companion animals can provide more reliable information in translational medicine (Kol et al, 2015;Hoffman and Dow, 2016).…”
Section: Introductionmentioning
confidence: 99%